High-gain rectangular-fins shaped balanced antipodal vivaldi antenna array extended by dielectric for wide-band imaging application - Shaikh, Faraz Ahmed; Khan, Sheroz; Alam, A. H. M. Zahirul; Ahmed, Syed Faiz; Shahid, Zeeshan; Khan, Talha Ahmed (IEEE, 2019)
In this paper, we propose an Ultra-wideband Balanced antipodal Vivaldi antenna embedded with equal rectangular shaped fins (RF-BAVA) for wide-band imaging application has been introduced. Further, dielectric substrate which elliptical in shaped with low permittivity constant value has been used in the extension of array antenna in H-plane in order to enhance the radiation characteristic of an antenna(RF-BAVA-D). The proposed single element of an antenna designed on special purpose dielectric-material Rogers RT/Duroid 5880 with thickness of 1.57mm and relative permittivity of ɛr = 2.2 by including 15 slits of same dimension on both arms of an antenna. The dimension of each element is 60.75mm x 66mm approximately. Particularly in the case of microwave imaging and its based application a stability of high gain is considered as an important requirement. So, the H-plane array-antenna principal approach has been adopted to improve antenna gain and polarization performance of array antenna based imaging system. The elements in H-plane almost cover entire ultra-wideband (3GHz-to-10.5GHz) frequency range with the reflection coefficient S11 < -10 dB. Based on the simulation results, the array elements with extended dielectric-director in H-plane arrangement offering high-gain up to 13dB with stable radiation pattern and good impedance bandwidth frequency on all ports while the single antenna element produces around 11dB. A targeted stable gain with low side-lobe level has been achieved in H-plane configuration with better directivity instead of single antenna element. The design and parametric evaluation of RF-BAVA-D has been verified using CST simulation software.